The Efficiency of the Triple P Program for Parents of Children with Type-1 Diabetes - Burcu Arkan; Ayşe Pınar Vural; Şafak Eray; Erdal Eren (Galenos Yayinevi, 2020)
Aim:The aim of this study was to investigate the effect of the Triple P-Positive Parenting Training Program, which was applied to the parents of children and adolescents with a type 1 diabetes (T1D) diagnosis aged 3-12 years, on parental attitude, parental mental health, and child behaviour.Materials and Methods:This research was conducted in a quasi-experimental manner. The sample of the research consisted of 32 parents who had children with a T1D diagnosis aged 3-12 years and who agreed to participate in the study. Data were collected using the Family Background Questionnaire, General Health Questionnaire, Strengths and Difficulties Questionnaire, Parental Attitude Research Instrument, Conflict Behaviour Questionnaire and Parent Satisfaction Questionnaire. The Group Triple P Programme was implemented with all groups for 8 weeks. Data were collected immediately after the programme. Data were evaluated by using multidirectional variance analysis, t- test and chi-square test.Results:It was shown that the Group Triple P applied to the parents of those children with a T1D diagnosis positively affects the mental health of the parents, their parental attitudes and the problematic behaviour of their children and also that the parents had less conflict with their children and the children had less conflict with their parents.Conclusion:It is suggested that further studies are carried out in different centres and cities with the Group Triple P Programme to widen the use of the Group Triple P Programme and also to plan future research where the Group Triple P programme and other programmes currently used in country can be compared.